X‐ray in‐line holography and holotomography at the NanoMAX beamline. (17th December 2021) - Kalbfleisch, Sebastian; Zhang, Yuhe; Kahnt, Maik; Buakor, Khachiwan; Langer, Max; Dreier, Till; Dierks, Hanna; Stjärneblad, Philip; Larsson, Emanuel; Gordeyeva, Korneliya; Chayanun, Lert; Söderberg, Daniel; et al.
Abstract : First results of in‐line holography and holotomography from the NanoMAX beamline at MAX IV are presented. Abstract : Coherent X‐ray imaging techniques, such as in‐line holography, exploit the high brilliance provided by diffraction‐limited storage rings to perform imaging sensitive to the electron density through contrast due to the phase shift, rather than conventional attenuation contrast. Thus, coherent X‐ray imaging techniques enable high‐sensitivity and low‐dose imaging, especially for low‐atomic‐number ( Z ) chemical elements and materials with similar attenuation contrast. Here, the first implementation of in‐line holography at the NanoMAX beamline is presented, which benefits from the exceptional focusing capabilities and the high brilliance provided by MAX IV, the first operational diffraction‐limited storage ring up to approximately 300 eV. It is demonstrated that in‐line holography at NanoMAX can provide 2D diffraction‐limited images, where the achievable resolution is only limited by the 70 nm focal spot at 13 keV X‐ray energy. Also, the 3D capabilities of this instrument are demonstrated by performing holotomography on a chalk sample at a mesoscale resolution of around 155 nm. It is foreseen that in‐line holography will broaden the spectra of capabilities of MAX IV by providing fast 2D and 3D electron density images from mesoscale down to nanoscale resolution.